The Oxford handbook of international security - Gheciu, Alexandra; Wohlforth, William Curti, 1959- (Oxford, United Kingdom : Oxford University Press, 2018)
This Oxford Handbook is the definitive volume on the state of international security and the academic field of security studies. It provides a tour of the most innovative and exciting news areas of research as well as major developments in established lines of inquiry. It presents a comprehensive portrait of an exciting field, with a distinctively forward-looking theme, focusing on the question: what does it mean to think about the future of international security?
Introduction -- Approaches to international security -- Major issues for twenty-first-century security -- Challenges and opportunities for twenty-first-century security -- Twenty-first-century international security actors.
Includes bibliographical references and index.
Keywords: Security, International; International relations